3D Space‐Confined Pyrolysis of Double‐Network Aerogels Containing In–Fe Cyanogel and Polyaniline: A New Approach to Hierarchically Porous Carbon with Exclusive Fe–Nx Active Sites for Oxygen Reduction Catalysis. Issue 8 (18th July 2017) - Zhang, Weiyu; Xu, Xiaocheng; Zhang, Chenxing; Yu, Zihuan; Zhou, Yiming; Tang, Yawen; Wu, Ping; Guo, Shaojun
Abstract : Iron and nitrogen co‐doped carbon (Fe–N/C) nanomaterials are promising non‐Pt catalysts toward the oxygen reduction reaction (ORR). Both spectroscopy and density functional theory studies reveal that Fe–N x accounts for the ORR activity. However, Fe–N/C catalysts prepared by traditional high‐temperature pyrolysis always contain less active Fe or Fe3 C nanoparticles, and it remains a great challenge to obtain Fe–N/C catalysts with high‐content Fe–N x active sites. Herein, a 3D space‐confined strategy for the pyrolysis of double‐network aerogels is reported, to obtain Fe–N/C network catalysts with exclusive Fe–N x active sites without the generation of Fe or Fe3 C nanoparticles. The as‐prepared Fe–N/C network exhibits more positive half‐wave potential, higher diffusion‐limited current density, and better selectivity for the ORR than catalysts derived from single aerogels and commercial Pt/C. Additionally, the ORR activity measured in potassium thiocyanate (KSCN) poisoned electrolyte corroborates that Fe–N x is the active site. This work opens a new guideline for designing the M–N/C catalysts with exclusive active sites in porous carbon matrices for boosting energy electrocatalysis. Abstract : An entirely new 3D space‐confined strategy is reported for the pyrolysis of double‐network aerogels to obtain Fe–N/C network catalysts with exclusive Fe–N x active sites without the generation of Fe/Fe3 C nanoparticles. The Fe–N/C network exhibits better oxygen reduction reaction (ORR) activity than catalysts derived from single aerogels and commercial Pt/C.